Latvių ežerų pavadinimų darybos specifika - Balode, Laimute (Baltistica, 1990)
THE SPECIFICITY OF DERIVATION OF LATVIAN NAMES OF THE LAKES The aim of this article is to determine a structural-derivational model of Latvian limnonyms, to compare this model with analogical systems of Lithuanian and as far as it is possible with those of the Prussian language. The structural-derivational analysis has been supplemented with a general survey of primary semantics of a toponym. As to the quantity, the first place among other structural-derivational types occupy compound genitive names of the lakes. The vast majority of those limnonyms are the names derived from other toponyms, most often from oikonyms. At present this type of derivation forces out all other topoderivational types (especially the primary names of the lakes). The second place occupies the mode of suffixal derivation of limnonyms. Latvian suffixal imnonyms are derived with the help of about 60 different suffixes, the most productive of these are deminutive suffixes -īt- and -iņ -. Inflexional limnonyms are derived with the use of the following flexions: -a, -e, -is, -us. There are 4 prefixes fixed (aiz-, ne-, pa-, pie-) with the help of which Latvian names of the lakes are derived. A comparison of the structural-derivational model of Latvian limnonyms with the corresponding models of Lithuanian and Prussian has shown that derivational types of lake names in those three Baltic languages coincide in general outlines; corresponding structural-derivational models are very close. Taking into account this fact, only quantitative difference is noticed (of course, we should bear in mind that the model of Prussian one can reconstruct only fragmentarily).